2021
DOI: 10.1186/s13041-021-00868-6
|View full text |Cite
|
Sign up to set email alerts
|

Diverse inflammatory threats modulate astrocytes Ca2+ signaling via connexin43 hemichannels in organotypic spinal slices

Abstract: Neuroinflammation is an escalation factor shared by a vast range of central nervous system (CNS) pathologies, from neurodegenerative diseases to neuropsychiatric disorders. CNS immune status emerges by the integration of the responses of resident and not resident cells, leading to alterations in neural circuits functions. To explore spinal cord astrocyte reactivity to inflammatory threats we focused our study on the effects of local inflammation in a controlled micro-environment, the organotypic spinal slices,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(59 citation statements)
references
References 74 publications
2
55
0
2
Order By: Relevance
“…Using an in vivo model for acute lung injury, namely lipopolysaccharide-instilled mice, it was shown that Cx43 hemichannels contribute to neutrophil transmigration towards the airspace [56]. Collectively, this could suggest a role for Cx43 hemichannels in neutrophil activation and transmigration in COVID-19 pathogenesis [3,7,21,22,57]. Furthermore, platelet aggregation and thrombosis, which occurs in the prothrombic phase and final phase of COVID-19, can develop towards multi-organ failure with death as outcome [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an in vivo model for acute lung injury, namely lipopolysaccharide-instilled mice, it was shown that Cx43 hemichannels contribute to neutrophil transmigration towards the airspace [56]. Collectively, this could suggest a role for Cx43 hemichannels in neutrophil activation and transmigration in COVID-19 pathogenesis [3,7,21,22,57]. Furthermore, platelet aggregation and thrombosis, which occurs in the prothrombic phase and final phase of COVID-19, can develop towards multi-organ failure with death as outcome [12].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to gap junctions, connexin hemichannels have a low open probability. They seem to become preferentially activated by pathological stimuli, such as decreased extracellular calcium concentrations, mechanical stimulation, oxidative stress, ischemia/reperfusion injuries, and inflammatory conditions [3][4][5]. Among the messengers permeating connexin hemichannels, adenosine triphosphate (ATP) plays a key role in the induction and exacerbation of inflammation [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory stimuli can lead to a rise in cytosolic Ca 2+ in sensory neurons, which facilitates the release of neurotransmitters, excitability, and pain ( 39 , 76 , 177 , 181 ). Studies showed that inflammatory cytokines increase spontaneous Ca 2+ oscillations in organotypic spinal cord slices ( 182 ). Intraplantar carrageenan or CFA injection in rats increased intracellular Ca 2+ in brain neurons or increased evoked Ca 2+ transients in DRG neurons, respectively ( 72 74 ).…”
Section: Mitochondrial Dysfunction In the Nervous System And Painmentioning
confidence: 99%
“…Inflammation disturbs OxPhos, promotes oxidative stress and Ca 2+ influx into the mitochondria via MCU. All these processes can induce mitochondrial fission ( 127 , 128 , 182 , 228 ). As such, inflammation is more likely to induce mitochondrial fission rather than fusion ( 229 ), but future research is needed to fully understand how fission and fusion contribute to pain in rheumatic disease.…”
Section: Mitochondrial Dysfunction In the Nervous System And Painmentioning
confidence: 99%
“…Specifically, while on DWCNT networks were composed by sparse neurons, on X-DWCNT neurons were organized in small clusters of cells, and their activity was differently shaped by synaptic inhibition. Interestingly, when applying tetrodotoxin (TTX 1 μM, a known blocker of action potential mediatedsynaptic activity; 44 ) we completely removed neuronal activity (Figure 7b, right traces) disclosing glial cells spontaneous calcium signaling (Figure 7e) 65 recorded as slow calcium episodes of longer duration in DWCNT samples when compared to X-DWCNT ones (13.5 ± 5 s for DWCNT and 10.1 ± 2.6 s for X-DWCNT, no parametric data, Mann− Whitney test, p < 0.05), as summarized by the box plot in Figure 7f, left. Interestingly, the frequency of glial events in pristine DWCNT was higher when compared to X-DWCNT one (0.008 ± 0.001 Hz for DWCNT, n = 8 cells, and 0.002 ± 0.0003 Hz for X-DWCNT, n = 7 cells; Figure 7f, right, p < 0.01).…”
Section: X-dwcnt Scaffold Favors the Formation Of Microclusters Of Pr...mentioning
confidence: 99%